Error Analysis of Polarimetric Interferometric SAR under Different Processing Modes in Urban Areas - Zexin LYU; Xiaolan QIU; Zhe ZHANG; Chibiao DING (Leida xuebao, 2022)
Polarimetric Interferometric Synthetic Aperture Radar (PolInSAR) simultaneously has interferometric height measurement and full-polarized detection capabilities, which can better reflect the structural properties of feature targets. Therefore, its potential for application in complex scenarios, such as urban areas, has attracted increasing attention. In urban areas, the processing mainly includes three modes: using interferometry to extract height based on polarimetric optimal coherence, using interferometry based on polarized decomposition, and associating polarimetric interferometric observation equations to retrieve the heights of different scattering mechanisms. The analysis of error factors and effects on Interferometric SAR (InSAR) and polarized SAR is almost complete, but the analysis of error effects under different processing modes of PolInSAR is insufficient. Based on the PolInSAR error model, our paper proposes a method for solving the scattering mechanism under the simultaneous polarization observation equation. Moreover, we derive the model including each error under different processing modes in PolInSAR from the aspect of polarized errors, interferometric errors, and the Signal-to-Noise Ratio (SNR). Furthermore, the model is verified through simulations, and we provide height inversion results through three processing modes after compensating for polarized errors and interferometric errors. After the error compensation, we obtain a Root Mean Squared Error (RMSE) in building areas of 2.77 m through polarimetric optimal coherence. Finally, the simulations provide the error impact curves under different processing modes of PolInSAR and compare the degree of different processing methods affected by errors, which provides a reasonable explanation for the design of the PolInSAR system, selection of processing methods, and data application.